oohh wait a second.. do i use Quadratic equation?
I need help solving for B in this equation:
(NOTE: 5b^2 is 5b squared)
5b^2 - 5b +1 = 0
I started by subtracting -1 from both sides getting:
5b^2 - 5b = -1
Then I pulled out 5b from the left side and got:
5b (b - 1) = -1
And now I have no idea what to do. I think I am doing the entire thing wrong. Can someone help me out?
Another way- which I personally prefer to just plugging into a formula: complete the square:
5b^2- 5b= -1 as you say. Divide through by 5:
b^2- b= -1/5.
(b- a)^2= b^2- 2ab+ a^2 will match that is 2a= 1 so a= -1/2 and a^2= 1/4.
We can make b^2- b into a "perfect square by adding 1/4:
b^2- b+ 1/4= -1/5+ 1/4= -4/20+ 5/20= 1/20
(b- 1/2)^2= 1/20= 1/(4(5))
as you say.